(untitled) (Vallis Aurea, 2016)
This paper provides the theoretical review of the fraud risk characteristics, systematization of the existing fraud knowledge and the causes of fraud occurrence. Moreover, it determines the roles and the responsibilities of managers and auditors in the fraud risk assessments. In addition, risk factors relating to the misstatements arising from fraudulent financial reporting have been examined. According to the results of numerous scientific and expert studies it is obvious that a system of internal controls, including fraud risk assessments as an elementary component of this system, contributes to reducing fraud occurrence. In order to gain information about the factors that could cause fraudulent financial reporting, the empirical research has been conducted on the sample of companies operating in the Republic of Croatia. The respondents, accountants and auditors, revealed how often they meet fraud risk factors. Although, according to respondents’ answers, companies rarely encounter circumstances that indicate the possibility of fraud, the obtained data imply that there are possibilities that financial statements contain misstatements as a result of fraud. Examples of circumstances indicating the possibility that the financial statements contain a material misstatement resulting from fraud include: last-minute adjustments that significantly affect financial results, followed by transactions that are not recorded in a complete or timely manner or are improperly recorded as to amount, accounting period, classification, or entity policy and unsupported or unauthorized balances or transactions. The problems, which the accountants most frequently encountered were undue time pressures imposed by management to resolve complex or contentious issues, an unwillingness to address identified deficiencies in internal control on a timely basis and missing documents.